2000
DOI: 10.4049/jimmunol.165.10.5428
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Microvascular Endothelial Cells Express the 180-kDa Macrophage Mannose Receptor In Situ and In Vitro

Abstract: Expression of the 180-kDa mannose receptor (MR) is mainly found on cells of the macrophage lineage. MR mediates the uptake of micro-organisms and host-derived glycoproteins. We demonstrate that endothelium of the human skin in situ and dermal microvascular endothelial cells (DMEC) in vitro expressed MR at both the protein and mRNA levels. In contrast, HUVEC were consistently negative for MR expression. DMEC internalized dextran as well as Escherichia coli by the way of MR into acidic phagosomes, only a few of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 49 publications
6
73
0
1
Order By: Relevance
“…According to our expression analysis (data not shown) and in line with an earlier report (47), dectin-1, the myeloid cell-expressed major receptor for fungal ␤-glucan, is not expressed by ECs thus excluding a role in Candidainduced endothelial signaling. Furthermore, the mannose receptor, another C-type lectin receptor, is absent in HUVEC (48). Thus, neither C-type lectin receptors nor TLR2 and TLR4 appear to be responsible for C. albicans-induced gene expression in our EC model.…”
Section: Discussionmentioning
confidence: 72%
“…According to our expression analysis (data not shown) and in line with an earlier report (47), dectin-1, the myeloid cell-expressed major receptor for fungal ␤-glucan, is not expressed by ECs thus excluding a role in Candidainduced endothelial signaling. Furthermore, the mannose receptor, another C-type lectin receptor, is absent in HUVEC (48). Thus, neither C-type lectin receptors nor TLR2 and TLR4 appear to be responsible for C. albicans-induced gene expression in our EC model.…”
Section: Discussionmentioning
confidence: 72%
“…Many differences have been reported between endothelial cells derived from the macrovasculature and the microvasculature (Groger et al, 2000;Salcedo et al, 2000;Otto et al, 2001) and angiogenic potential in response to GRP seems to be another one of them. Since new blood vessels sprout from the microvasculature, the lack of angiogenic response in HUVECs is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…33 Immunohistological studies performed on human placental and skin epithelia have, however, shown that endothelial cells express generally Fc␥RII but not Fc␥RIII. [33][34][35][36] In particular, fetal endothelial cells in human placenta have been shown to express a single type of Fc␥R, namely, Fc␥RIIb2. 37 Hunziker and Mellman 38 showed that Fc␥RIIb2 transfected into polarized cells is capable of mediating transcytosis of IgG.…”
Section: Discussionmentioning
confidence: 99%